Assessment of trade-offs between timber and carbon values of Pterocarpus angolensis (Kiaat) in the Kavango Region of Namibia : a comparison of current and potential values - Moses, Moses (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFor)--Stellenbosch University, 2013.